MASS AND MOMENTUM TRANSFER TO ELLIPSOIDAL BUBBLES AND DROPS (Journal of Engineering, 2002)
Semi-analytical solution for the resistance of the flow and convective heat and mass transfer over the surface of ellipsoidal bubble and a drop were obtained. The fluid flow solution utilized the viscous dissipation and the heat transfer solution was based on the integral method. New relations for the drag force and the convective heat and mass transfer coefficients were derived and compared with the available theoretical solutions and experimental correlations. The range of Reynoks number was from I to 100 and Weber number from 0 to 3.23.